Literature Review : Strategi Manajemen Sumber Daya Manusia dalam Meningkatkan Daya Saing dan Ketahanan Organisasi Pendidikan - Indah Fauzia Isya Putri; Khoerotun Nisa; Is'af Qushoyina Tsuraya; Mohammad Rizal Fauzi; Moh. Syakir Mujahid; Fita Ardianti Rohmah; Mu’alimin Mu’alimin (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This literature review investigates the role of HRM as a strategic factor in boosting institutional performance, competitiveness, and organizational resilience in educational institutions. By analyzing five selected academic articles, the study identifies three core HRM approaches: best practices, contingency, and configurational models. Key focuses include competency development, technological integration, and transformational leadership in fostering a productive and adaptive work environment. Findings reveal that strategic HRM significantly contributes to organizational sustainability amid global challenges. The study recommends a human-centered, data-driven approach to establish a sustainable HRM framework for educational institutions.